DIGITAL MARKETING MANAGEMENT TRAINING FOR FAMILY WELFARE EMPOWERMENT MEMBERS IN BANDUNG REGENCY - Tayo, Yanti; Nursanti, Siti; Utamidewi, Wahyu; Mayasari, Mayasari; Abidin, Zainal (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
There is no denying that the COVID-19 pandemic, which broke out at the start of 2020, had an influence on Indonesia's family economy, both positively and negatively. A decline in family income levels is one of the COVID-19 pandemic's negative effects on Indonesian families, although there are also beneficial effects, such as increased usage of digital technologies worldwide, including in Indonesia. Teaching women how to be productive without having to leave the house while still being able to fulfil their responsibilities as mothers is one of the answers suggested by academics from Singaperbangsa Karawang University. This time at the community service, the volunteer proposes a way to improve mothers' knowledge by giving them training in operating digital stores using their social media. This service will be provided to mothers who are members of the Bandung Regency Family Empowerment and Welfare Group of mothers. Participants in this programme should gain an understanding of how women can manage digital shops to boost family income.